Trust–Privacy-Based User Acceptance Model for Location-Based Mobile Navigation Services: Conceptual Development and Research Propositions - Atta Ur Rahman; Fuyang Ke; Muhammad Raza (Methods in Science and Technology Studies, 2026)
The two most important factors for location-based mobile navigation services are navigation performance and trusted data governance, especially when location data is used repeatedly. Previous studies have tended to focus on privacy concerns, perceived risk, trust, transparency, control, and service quality separately or in settings other than consumer navigation, as is the case in this study. As a result, the interaction between privacy risk perceptions and provider assurances in influencing mobile navigation acceptance remains poorly defined. This conceptual study develops a trust- and privacy-based user acceptance framework by synthesizing the literature through a structured procedure and incorporating the Technology Acceptance Model, Privacy Calculus Theory, and Trust Theory. The framework posits that privacy concern increases perceived risk, while privacy concern and perceived risk reduce trust. In contrast, transparency, perceived control over location data, and service reliability can enhance trust. The roles of perceived usefulness and user acceptance intention in the pathway to user acceptance remain unchanged, suggesting that trust is an antecedent to perceived usefulness and user acceptance intention. The framework fills the theoretical gap between privacy-risk assessment and trust-building service attributes, and between trust in technology acceptance and repeated disclosure of the location setting. It also recognizes the need for transparent data practices, meaningful location control, and reliable service performance as provisional design priorities, which require future empirical validation. The propositions are to be used as a starting point for further testing on platforms, providers, user groups, cultures, and regulatory frameworks.